(untitled) (Annals of Bangladesh Agriculture, 2023)
Thirty-five country bean (Lablab purpureus L.) genotypes collected from coastal belts of Bangladesh were screened for tolerance to a high level of salinity (12 ds m-1 NaCl) in Hogland nutrient solution in a hydroponic system at vegetative growth stage. The experiment was conducted in a complete randomized design with three replications at Genetics and Plant Breeding lab, BSMRAU during January-February, 2016. The genotypes were varied in biochemical properties (proline, carbohydrates, chlorophyll contents etc.), dry root: shoot ratio, relative shoot dry weight and salt susceptibility index (SSI). Wide variation among the genotypes was noticed for root and shoot ratio (p<0.05). Relative shoot length varied from 29.87- 126.04 with an average of 79.29 whereas relative root length showed wide variation with a range of 20.00-300.00. Relative root dry weight (RRDW) varied from 22.06-211.43 with a mean of 79.40 and relative shoot dry weight (RSDW) ranged from 26.57-192.66 with an average of 69.29. Relative root : shoot ratio showed a range of 0.59 to 2.51. On the basis of relative performance of root-shoot dry matter, dry leaves weight, root-shoot ratio, six genotypes were found highly tolerant, seven were moderately tolerant, sixteen were moderately susceptible and six were highly susceptible to salinity stress. Based on visual observation of plants, relative shoot dry weight (RSDW), proline content, total sugar and soil plant analysis development (SPAD) value the genotypes CB031, CB035, CB003, CB023, CB026, CB028, CB013, CB030, CB014, CB024, CB019, CB020 and CB002 were selected as tolerant for further evaluation and use in breeding work. Ann. Bangladesh Agric. (2022) 26 (2) : 19-31